2022
DOI: 10.1002/ces2.10150
|View full text |Cite
|
Sign up to set email alerts
|

60 years of dislocations in ceramics: A conceptual framework for dislocation mechanics in ceramics

Abstract: High‐tech ceramics are typically engineered by controlling point defects and interfaces while one‐dimensional dislocations have found much less attention so far. Nevertheless, their impact on almost any functional property and the sudden ease to fabricate them with novel synthesis methods, such as rapid densification, brings spotlight attention to dislocations as design dimension. Although the typical brittleness of ceramics insinuates the irrelevance of dislocations for mechanical behavior, abundant literatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 226 publications
0
14
0
Order By: Relevance
“…Dislocations in ceramics have been investigated since the 1950s, most prominently by Gilman and Johnston in LiF 4–8 . An overview of the current understanding of the general dislocation mechanics in ceramics has been provided by Porz recently 9 . The understanding of dislocation nucleation, multiplication, and motion proposed by Gilman and Johnston can be borrowed to lay the foundation for the dislocation mechanics in ceramics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dislocations in ceramics have been investigated since the 1950s, most prominently by Gilman and Johnston in LiF 4–8 . An overview of the current understanding of the general dislocation mechanics in ceramics has been provided by Porz recently 9 . The understanding of dislocation nucleation, multiplication, and motion proposed by Gilman and Johnston can be borrowed to lay the foundation for the dislocation mechanics in ceramics.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7][8] An overview of the current understanding of the general dislocation mechanics in ceramics has been provided by Porz recently. 9 The understanding of dislocation nucleation, multiplication, and motion proposed by Gilman and Johnston can be borrowed to lay the foundation for the dislocation mechanics in ceramics. On the other hand, recently the dislocation-mediated functional properties in ceramics have attracted increasing research interest, be it superconductivity, 10 electrical conductivity, 11 or ferroelectric properties.…”
Section: Introductionmentioning
confidence: 99%
“…It was suggested that engineering dislocation sources to circumvent dislocation nucleation may be a feasible way to promote dislocation plasticity in ceramics. 34 An example of such is, as discussed before, flash-sintered TiO 2 that contains a high density of dislocations and stacking faults and can exhibit plastic strain up to ∼12% during room-temperature pillar compression, 65 while conventionally sintered, dislocation-free TiO 2 samples have a fracture strain of ∼2%. In this sense, the previously presented cyclic Brinell indentation and cyclic scratching methods show consistent results: during the first cycle of indentation/scratching, fresh dislocations with a medium density are produced, which serve as effective sources for upcoming deformation cycles.…”
Section: Correlation and Competitionmentioning
confidence: 98%
“…2,[36][37][38][39][40][41] A recent survey of dislocation mechanics in ceramics is given in reference. 42 Molecular dynamics simulations of edge dislocations within basal and pyramidal planes of sapphire have been conducted by many investigators, as reported, for example, in references. 43,44…”
Section: F I G U R Ementioning
confidence: 99%
“…This gives rise to plastic deformation by gliding of four partial dislocations separated by stacking faults 2,36–41 . A recent survey of dislocation mechanics in ceramics is given in reference 42 . Molecular dynamics simulations of edge dislocations within basal and pyramidal planes of sapphire have been conducted by many investigators, as reported, for example, in references 43,44 …”
Section: Introductionmentioning
confidence: 99%